2008
DOI: 10.1007/s11214-008-9378-4
|View full text |Cite
|
Sign up to set email alerts
|

First Results from the THEMIS Mission

Abstract: Abstract. THEMIS was launched onDuring the coast phase the probes were put into a string-of-pearls configuration at 100s of km to 2R E along-track separations, which provided a unique view of the magnetosphere and enabled an unprecedented dataset in anticipation of the first tail season. In this paper we describe the first THEMIS substorm observations, captured during instrument commissioning on March 23, 2007.THEMIS measured the rapid expansion of the plasma sheet at a speed that is commensurate with the simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 184 publications
(200 citation statements)
references
References 35 publications
5
194
0
1
Order By: Relevance
“…[38] Fast azimuthal plasma flows in the near-Earth plasma sheet have been detected in past studies [e.g., Yeoman et al, 1998;Nakamura et al, 1999;Angelopoulos et al, 2008b]. Using a network of ground magnetometers, Yeoman et al [1998] showed an azimuthal ionospheric feature propagating eastward with a speed of ∼6 km/s that was associated with magnetic dipolarization and fast dawnward plasma flow observed by the Geotail spacecraft located in the near-Earth plasma sheet ∼4 h MLT to the east of the ionospheric disturbances.…”
Section: Discussionmentioning
confidence: 88%
“…[38] Fast azimuthal plasma flows in the near-Earth plasma sheet have been detected in past studies [e.g., Yeoman et al, 1998;Nakamura et al, 1999;Angelopoulos et al, 2008b]. Using a network of ground magnetometers, Yeoman et al [1998] showed an azimuthal ionospheric feature propagating eastward with a speed of ∼6 km/s that was associated with magnetic dipolarization and fast dawnward plasma flow observed by the Geotail spacecraft located in the near-Earth plasma sheet ∼4 h MLT to the east of the ionospheric disturbances.…”
Section: Discussionmentioning
confidence: 88%
“…The method used in our previous studies has the advantage that it enables us to investigate both temporal and spatial variations in various parameters based on a minimum number of assumptions, and that it offers a perspective view of substorms. Here we focus on both the structure in the X-Z plane and temporal evolution in the equatorial plane using data from the five THEMIS probes (Angelopoulos et al, 2008a) to perform a superposed-epoch analysis. Magnetic-field data and plasma-moment data obtained with the Flux Gate Magnetometer (FGM) (Auster et al, 2008), Electrostatic Analyzer (ESA) and Solid State Telescope (SST) (McFadden et al, 2008) instruments onboard the THEMIS probes (each with 3 s time resolution) are used.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Пять спутников THEMIS (масса одного КА -128 кг) были запущены в 2007 г. [7]. Эти спутники бы-ли реализованы на уже имевшейся у американских коллег малой платформе SMEX и имели на бор-ту достаточно простой набор из пяти стандартных приборов.…”
Section: высокоапогейные спутникиunclassified